Digital Parenting to Protect Children from Internet Addiction at Muhammadiyah Elementary School Klopogodo - Rahmatullah, Azam Syukur; Fitriah, Fitriah; Putro, Khamim Zarkasyi (Edumedia Solution, 2024)
Technology is an incredibly useful breakthrough in helping us with our daily activities, and one of them is the internet. The internet is a network system that covers the entire world through telecommunication channels such as telephone, radio links, satellites, and so on. Indeed, the internet provides significant benefits for education, research, business, and various aspects of life. However, behind these great benefits, the internet also has negative aspects. One of the negative impacts often associated with the internet is addiction or internet addiction. Internet addiction is a syndrome characterized by spending a considerable amount of time using the internet and being unable to control its usage when online. The side effects include anxiety, depression, declining physical health, declining mental health, and even disruption of daily activities. Internet addiction can be experienced by anyone and any institution, including Muhammadiyah Elementary School in Klopogodo, Gombong District, Kebumen. There are several efforts that can be made to reduce the negative impact and protect children from internet addiction, one of which is using the digital parenting method. Digital parenting is a method used to protect children from internet addiction by providing clear boundaries regarding what is allowed and what is not allowed when using digital devices and the internet. Digital parenting implemented at Muhammadiyah Elementary School in Klopogodo has had a significant positive impact. Teachers have felt the benefits of digital parenting, as it has made children more obedient in using their phones. Limiting phone usage, restricting applications, and controlling access to certain content have greatly helped parents in parenting.